Integral Averaging Technique for Oscillation of Elliptic Equations of Second Order (Journal of Partial Differential Equations, 2003)
" The elliptic differential equations of second order \\sum^n_{i,j=1}D_i[A_{ij}(x, y)D_jy] + P(x, y) + Q(x, y, \u2207y) = e(x), x \u2208 \u03a9 . will be considered in an exterior domain \u03a9\u001a\u2282 R^n, n \u2265 2. Some oscillation criteria are given by integral averaging technique."